The Passage of Time Between the Commission of an Offence and Sentencing as a Ground for Punishment Mitigation (Ius Novum, 2025)
This paper addresses the issue of rational sentencing in criminal proceedings, focusing specifically on the significance of the passage of substantial time between the commission of an offence and the imposition of a sentence as a potential ground for extraordinary mitigation of punishment. The aim is to resolve the question of whether a significant lapse of time between the commission of an offence and sentencing may serve as a mitigating factor in the punishment imposed by the court for that offence, or, more specifically, whether it may justify extraordinary mitigation of the statutory penalty or constitute a circumstance warranting leniency within the ordinary sentencing framework. The research hypothesis assumes that a lengthy interval between the offence and adjudication may exert a mitigating influence on the sentence imposed, both in cases where the court applies a sentence within the ordinary sentencing framework and where it resorts to extraordinary mitigation, although the time lapse does not constitute an autonomous basis for such mitigation. The study employs the dogmatic method, understood as an analysis of legal norms, with reference to relevant judicial decisions and the views of legal academics and commentators.
Keywords: judicial sentencing, extraordinary mitigation of punishment, mitigating circumstances, time in criminal law